Humanized Education for a More Humanly Democratic Democracy - Contreras-Salinas, S (UNIV COSTA RICA, EDITORIAL, 2020)
Acknowledging that schooling comprises a complex and contradictory gamut of ideological and material procedures that juxtapose specific lifestyles to transform life experiences, this article proposes certain possibilities or clues to render the ethical-political dimension of education as more humane and humanistic and contribute to building another type of democracy, given that today s democracy is based on a post-dictatorship, neoliberal, logical perspective and emphasizes formal rather than substantial aspects of democracy. This implies including human rights as part of education and, thus, contribute to how students develop affective and semantic attachments in their attempt to regulate ideas and give their lives meaning, thereby, permeating the ordinariness of the current system. The conclusion highlights the need to consider the ethos of democracy, imbued with an ethics of cordiality that distorts aspects such as poverty, exclusion, commercial exploitation and corruption. Finally, the need to discuss the transformational potential of education is proposed.